(untitled) (REMUNOM, 2025)
Child and adolescent mental health is an increasingly evident concern in our society. Among all life cycles, early life is possibly where the most significant changes occur. For a long time, only the physiological aspects of growth were observed. However, with the intense cultural, technological, social, and family changes of recent decades, the concern about understanding how children’s and adolescents’ emotional health develops has emerged. Thus, this article aims to conduct a bibliographic review of the past four years on how children’s and adolescents’ mental health is addressed in Brazil and seeks to understand the diagnostic process and its implications, such as pathologization and medicalization. Additionally, it aims to identify intersections, psychosocial, and environmental determinants that may cause psychological distress and outline possible intervention strategies based on literature and successful experiences.